Photodegradation of chlorophenoxyacetic acids by ZnO/y-Fe2O3 nanocatalysts : a comparative study - Abdullah, Abdul Halim; Lee, Kian Mun; Zainal, Zulkarnain; Hussein, Mohd Zobir (Canadian Center of Science and Education, 2013)
ZnO/γ-Fe2O3 nanocomposite was synthesized via simple precipitation. The synthesized nanocatalysts underwent heat treatment at 450oC for an hour. The characteristics of the nanocomposite were investigated by XRD, TEM, and BET surface area measurement. Zeta potential analysis was used to examine the surface charge properties of the nanocatalysts. The synthesized nanocomposite has an average particle size of 11 nm and a surface area of 20 m2 g-1. The potential of ZnO/γ-Fe2O3 as a photocatalyst was evaluated by photodegrading chlorophenoxyacetic acids (PAA, 2,4-D, 2,4,5-T and 4CA). The decomposition of chlorophenoxyacetic acids by ZnO/γ-Fe2O3 followed 4CA > 2,4,5-T ≈ 2,4-D > PAA. The result indicates the applicability of ZnO/γ-Fe2O3 nanocomposite as a photocatalyst in removing organic pollutants in wastewater.